Barriers experienced by nurses working in psychiatric wards in caring for patients with mental disorders: A qualitative study - Roghaieh Keykha; Naima Seyedfatemi; Seyedeh Narjes Mousavizadeh; Parvaneh Vasli (Nursing Practice Today, 2025)
Background & Aim: Providing quality care to hospitalized psychiatric patients is vital, but many barriers hinder it. This study aimed to identify the barriers faced by nurses working in psychiatric wards in providing care for inpatients with mental disorders. Methods & Materials: This qualitative study used a conventional content analysis approach and was conducted from July 2023 to September 2024 in three hospitals in Iran. Twenty psychiatric nurses with at least six months of experience were selected through purposive sampling. Data were collected through 20 semi-structured interviews (about 45 minutes each) and analyzed using conventional content analysis with MAXQDA software (Version 10). Results: The findings revealed two main categories of barriers that psychiatric nurses face. The first, individual-social-professional factors, include nurses' inappropriate perceptions and actions, societal and family misconceptions about psychiatric care, and mental fatigue. The second, organizational-managerial factors, include staff shortages in both quantity and quality, excessive workload, management misunderstandings about psychiatric care, lack of organizational support, lack of effective guidelines, unfavourable physical environment, inadequate healthcare and recreational facilities, and lack of financial support for nurses. In particular, lack of knowledge about mental disorders and perceived institutional neglect emerged as major barriers that significantly reduced nurses' motivation and compromised the overall quality of psychiatric care. Conclusion: This study highlights the complex barriers to optimal psychiatric care. Overcoming these challenges through targeted interventions, such as enhancing professional support systems and organizational reforms, is essential to fostering a more conducive care environment. These measures can improve psychiatric care quality.